A Spatial Dengue Risk Map for the Jaffna District of northern Sri Lanka - Jayadas, T.T.P.; Bharathy, P.; Gajapathy, K.; Suthakar, K.; Arasaratnam, V.; Kumanan, T.; Surendran, S.N. (University of Jaffna, 2023)
Dengue, a mosquito-borne disease, is a major public health concern in Sri Lanka including the northern Jaffna district. Epidemiology of dengue is associated with variations in land-use patterns and socio-economic factors. Jaffna district is one of the administrative locations with high incidence of dengue over the last two decades. The objective of the study was to identify potential dengue risk areas based on land-use patterns and socio-economic and demographic factors in Jaffna district at the Medical Officer for Health (MoH) administrative level applying spatial multi-criteria analysis using Geographic Information System Platform. The analysis also incorporated dengue cases and dengue serotypes identified in 2019 in the Jaffna district. The study reveals that the Nallur MoH division is the very highrisk area for dengue transmission. The identified risk map is expected to be useful for health authorities to prioritize control measures to identified risk areas. A detailed study considering land-use pattern, socio-economy, demography and serotypes over the years is warranted to understand the spatiotemporal patterns in dengue transmission in the Jaffna district.
Keywords: Dengue; Geographic information system; Jaffna district; Risk map; Multi-criteria analysis; DENV serotypes; Sri Lanka